2017
DOI: 10.1016/j.bbr.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hypomagnesemia alters hippocampal NMDAR subunit expression and programs anxiety-like behaviour in adult offspring

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.  Maternal Mg deficiency reduced hippocampal GluN1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
7
0
3
Order By: Relevance
“…The following experiments were focused on the BLA of amygdala, because, according to behavioral studies, the BLA is implicated in the onset and development of anxiety [30], a behavioral abnormality that has been associated with synaptic changes [31] and expression alteration of NMDAR [32]. The levels of NMDAR in the BLA of mice were examined on the 16th day (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The following experiments were focused on the BLA of amygdala, because, according to behavioral studies, the BLA is implicated in the onset and development of anxiety [30], a behavioral abnormality that has been associated with synaptic changes [31] and expression alteration of NMDAR [32]. The levels of NMDAR in the BLA of mice were examined on the 16th day (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Magnesium deficiency has been shown to impair foetal growth and alter kidney function leading to increased urination in the offspring . Furthermore, magnesium deficiency during pregnancy in mice has been shown to induce anxiety like behaviour in adulthood . A population based birth cohort study demonstrated that maternal zinc deficiency is associated with foetal growth restriction .…”
Section: Long Term Effects Of Micronutrient Deficiencies On Offspringmentioning
confidence: 99%
“…15 Furthermore, magnesium deficiency during pregnancy in mice has been shown to induce anxiety like behaviour in adulthood. 16 A population based birth cohort study demonstrated that maternal zinc deficiency is associated with foetal growth restriction. 17 Furthermore, zinc deficiency in rats during the pre and postnatal period induced sex specific vascular dysfunction in offspring.…”
Section: Magnesium Deficiency Hasmentioning
confidence: 99%
See 1 more Smart Citation
“…Магнийдефицитное состояние в период беременно-сти значимо приводит к повышению до-и постимпланта-ционной гибели плодов, снижает их массу и размеры [26]. Кроме того, доказано, что гипомагнезиемия у матери во время беременности приводит к нарушениям памяти у потомства [27]. В то же время прием препаратов магния во время беременности значительно снижает риск раз-вития синдрома задержки роста плода, а также уровень провоспалительных цитокинов в амниотической жидко-сти и плаценте [28].…”
unclassified